2004
DOI: 10.1021/bi035455q
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Different Methylation States of Chemotaxis Receptor Tar by Receptor Methyltransferase CheR

Abstract: Bacterial chemotaxis receptors are posttranslationally modified by carboxyl methylation of specific glutamate residues within their cytoplasmic domains. This highly regulated, reversible modification counterbalances the signaling effects of ligand binding and contributes to adaptation. Based on the crystal structure of the γ-glutamyl-methyltransferase CheR, we have postulated that positively charged residues in helix α2 in the N-terminal domain of the enzyme may be complementary to the negatively charged methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Initial rates of methylation were determined with saturating concentrations of receptors using concentrations of T. maritima CheR at which rates were linearly proportional to enzyme concentration ( Table 1). The data indicate that T. maritima receptors can be efficiently methylated in vitro at rates comparable to that previously reported for S. enterica receptor methylation at 30°C (1.1 mol CH 3 · mol CheR Ϫ1 · min Ϫ1 [24]). As expected, for all substrates, the methylation rates for both full-length receptors and cytoplasmic domains increased as the temperature was increased up to 70°C.…”
Section: Resultssupporting
confidence: 86%
“…Initial rates of methylation were determined with saturating concentrations of receptors using concentrations of T. maritima CheR at which rates were linearly proportional to enzyme concentration ( Table 1). The data indicate that T. maritima receptors can be efficiently methylated in vitro at rates comparable to that previously reported for S. enterica receptor methylation at 30°C (1.1 mol CH 3 · mol CheR Ϫ1 · min Ϫ1 [24]). As expected, for all substrates, the methylation rates for both full-length receptors and cytoplasmic domains increased as the temperature was increased up to 70°C.…”
Section: Resultssupporting
confidence: 86%
“…Structurally, the Glx pair and small residues in the motif lie in adjacent turns on the solvent-exposed side of a methylation helix. One residue of the Glx pair is the target for methylation by CheR and for deamidation and demethylation by CheB and CheD, a receptor-modifying deamidase lacking from E. coli but typical of many chemotaxis systems (29), whereas the flanking small residues are thought to be important for correct docking at the helix by the adaptation enzymes (30,31). We collected sequences from each signaling class containing the methylation subdomain, where a Glx pair was identified in the bc heptad registers predicted to be on the solvent-exposed surface of the four-helix bundle and determined the consensus methylation sequence for each class.…”
Section: Resultsmentioning
confidence: 99%
“…1E). negatively charged methylation site [45]. Intriguingly, sequence analysis revealed that these residues were also conserved in BsCheR (as Lys23 and Arg30) ( Fig.…”
Section: Structure Of Bscher and Structural Comparison With Stchermentioning
confidence: 82%
“…2C), have shown to be involved in the substrate recognition and binding to the methylation site [45]. Studies on CheR of S. typhimurium established the involvement of Arg53 in methyl transfer reaction, and its location in the active site, with the methylation sequence of the receptor that is oriented antiparallel to α2 helix of CheR [45]. Arg53 may stabilize or position methylatable γ-carboxlate of glutamate by ion-pair, salt-bridge A c c e p t e d M a n u s c r i p t or other electrostatic interaction.…”
Section: Active Site and Comparison Of Sah Bindingmentioning
confidence: 99%